Immunomodulatory activity of Apis mellifera propolis from the North of Argentina - Sampietro, Diego Alejandro (2016)
Propolis is a bee hive product with complex chemical composition that was used as medicine from ancient times. The immunomodulatory activity of partially purified propolis extracts (PPPEs), galangin and pinocembrin was studied through their in vitro effect on neutrophil chemotactic and phagocytic activities. PPPEs (15 samples from each of 10 different beehives) were more effective (around 45% and 50% for a concentration of 40 μg of PPPEs/mL of active substance) as chemotactic agents than galangin and pinocembrin (around 20 and 25%, respectively) and showed higher neutrophil phagocitic activity (270 ± 10% for beehive 10) than galangin and pinocembrin (180 ± 10 and 135 ± 9%, respectively). The highest effect of PPPEs can be attributed to a synergistic effect among components of PPPEs. The results of this study indicated that PPPEs, galangin and pinocembrin stimulate neutrophil chemotactic activity at various concentrations suggesting their possible use for patients suffering neutrophil disfunction. The nitro blue tetrazolium results indicated that the extracts and isolated flavonoids have the capacity to scavenge active radicals suggesting that they would be valuable in the treatment of diseases associated with free radical damage. Consequently, the in vitro results suggest a potential value of these propolis extracts in the medical field.